Reactive Diffusion Model in Determining Dissolution Rate of Edible Electronics Materials - Sihombing, Yuan Alfinsyah; Sawitri, Asti; Rodhiyah, Marathur (Talenta Publisher, 2026)
Edible electronic materials have emerged as an attractive research with broad potential applications. In the healthcare field, these materials can be utilized for diagnosing, monitoring, and treating organs within the gastrointestinal tract. A key characteristic of these materials is their ability to be digested and dissolved in water or bodily fluids. This study aims to theoretically investigate and predict the dissolution behavior of edible electronic materials using a one-dimensional (1D) reactive diffusion model. This model indicates that the dissolution behavior is governed by two primary parameters: the reaction rate constant (k) and the water diffusivity (D). Materials such as magnesium (Mg), zinc (Zn), and molybdenum (Mo) exhibit average dissolution rates ranging from 2.51 × 10-12 cm s-1 to 3.40 × 10-8 cm s-1 for diffusivity values between 10-17 and 10-10 cm2 s-1. In addition, the ratio of effective thickness to initial thickness (h/h0) increases and is influenced by the molar mass of the material, following the order Mo > Zn > Mg. The dissolution rate modeling results demonstrate that the reactive diffusion model is capable of representing trends that are consistent with experimental observations.